"Pay for Quality" (P4Q) as a quality strategy. (13th November 2019) - Quentin, W; Eckhardt, H; Smith, P
Abstract: P4Q can be implemented in various health care settings, targeting a range of health care providers or professionals. P4Q schemes can reward high quality measured in terms of structures, processes, and/or outcomes, and/or penalise low quality and are implementable in line with other quality improvement interventions. This presentation aims to clarify the concept of P4Q, highlight the use of P4Q schemes in different settings in European countries, and systematize the evidence on the effectiveness, cost-effectiveness and implementation of P4Q as a quality strategy. We could identify fourteen primary care P4Q programmes and thirteen hospital P4Q programmes in a total of 16 European countries. P4Q schemes in primary care incentivise mostly process and structural quality with respect to prevention and chronic care. P4Q schemes in hospital care prioritize improvements in health outcomes and patient safety. Studies suggest small positive effects on process-of-care (POC) indicators in primary care but not in hospital care. Evidence on health outcomes and patient safety indicators is inconclusive. Cost-effectiveness is unlikely because of lacking effectiveness. P4Q schemes are more effective when the focus of a scheme is on areas of quality where change is needed and if the scheme embraces a more comprehensive approach, covering many different areas of care; however, such programmes are generally technically and politically difficult to implement. In this light, this presentation will conclude with a number of recommendations, both technical and policy-oriented.